Endocan as a potential biomarker of disease severity and exacerbations in COPD - In, Erdal; Kuluozturk, Mutlu; Turgut, Teyfik; Geckil, Aysegul Altintop; Ilhan, Nevin (Wiley, 2021)
Introduction: Endocan is a proteoglycan that is regarded as a novel marker of endothelial dysfunction. Endothelial dysfunction in pulmonary vascular bed is known to play an important role for the pathogenesis of COPD. Objective: This study aimed to determine serum endocan levels in patients with stable COPD and acute exacerbation of COPD (AECOPD) and to test the relationship between serum endocan levels and exacerbations. Methods: This study enrolled a total of 55 COPD patients, 24 of which had AECOPD and 31 had stable COPD. All patients' basic demographic and clinical data were recorded and blood samples were collected. Results: Serum endocan levels were significantly higher in the AECOPD group compared to the stable COPD and control groups (for both p < 0.001) and stable COPD group had higher levels than the control group (p < 0.005). Additionally, serum endocan levels were negatively correlated with FVC, FEV1, partial oxygen pressure and oxygen saturation (r = -0.30, p = 0.03; r = -0.34, p = 0.01; r = -0.34, p = 0.01 and r = -0.36, p = 0.007 respectively), and positively correlated with disease duration and systolic pulmonary artery pressure (r = 0.47, p < 0.001; r = 0.31, p = 0.02 respectively). A cut-off value of 434.29 pg/ml for endocan predicted exacerbation with a sensitivity of 79% and a specificity of 84% (AUC: 0.778, 95% Cl 0.648-0.909; p < 0.001). Logistic regression analysis revealed that increased endocan levels was independent predictor of COPD exacerbation (OR = 9.32, 95%CI, 1.64-52.95; p = 0.01). Conclusion: Endocan may be a novel biomarker for detection of endothelial dysfunction and prediction of exacerbations in patients with COPD.
Keywords: chronic obstructive pulmonary disease; endocan; endothelial cell specific molecule-1; endothelial dysfunction; systemic inflammation